Spirituality of Later Life : On Humor and Despair. - Mackinlay, Elizabeth (Routledge, Taylor & Francis Group, 2012)
Humor expresses a certain heroic defiance in the face of life's most challenging experience and provides a valuable resource for the celebration of life and the divine comedy of faith, hope, and love. From the book chapter by Melvin A. Kimble, PhD Studies have shown that as many people age, their spirituality deepens. Spirituality of Later Life: On Humor and Despair explores the challenges faced by those in later life and the use of humor for self-transcendence to achieve greater strength and deeper spirituality.